Estudo das alterações lineares na região cervical de blocos M.O.D. fundidos em liga de cobre alumínio, segundo as técnicas de expansão higroscópica e térmica. - Lopes, D.; Bausells, J.; Mendes, A. J. (My University, 1990)
The authors studied linear alterations processed on copper-aluminum casten MOD blocks, obtained from two expansion techniques (termic and hygroscopic by immersion). UNITERMS: Investment expansion. Thermic expansion. Hygroscopic expansion. Casten Technique.
Linear changes in the cervical region of M.O.D. blocks cast in copper aluminum alloy with hygroscopic expansion and thermic techniques
Keywords: aluminum; biomedical and dental materials; copper; dental alloy; chemistry; denture; heat; Aluminum; Copper; Dental Alloys; Dental Casting Investment; Dental Casting Technique; English Abstract; Heat